(untitled) (Huellas, 2016)
Addressing current social problems of the European continent such as nationalism, cannot be considered without setting them in the proper context, analyzing the processes that have characterized the history and formation of European societies. In this regard, this paper gathers and analyses the contribution of different authors to describe one of the military events that characterized the twentieth century: the wars in the Balkan area. Understanding the same approach implies understanding the multi-causal analysis of conflicts, given mainly by ethnic and religious conditions, as well as by the no less important political, economic, historical and international factors. Also, the analysis of events can advance critical thinking, due to the understanding of international pressures that acted as catalysts of the wars. The fragmentation of the former Yugoslavia resulted in countries that are not out of the economic crisis experienced for years, so nationalistic feelings are shaping the scene of the “Yugonostalgia”.